Evaluation of different drying models for jabuticaba peel, dried in spouted bed dryer through performance indicators and the impact on anthocyanins - Oliveira Júnior, Antonio Martins; Santos, Jéssica Teles Sirqueira; Souza, Domingos Fabiano Santana (Scientia Plena, 2018)
Jabuticaba fruit stands out for its energetic and nutritional value being widely consumed in the fresh form and used for the production of jellies, vinegar, wines, and liquor. The jabuticaba peel has a high content of natural antioxidants, such as carotenoids, anthocyanins, tocopherols, and phenolic compounds, these compounds give protection to the fruit. In order to promote preservation of the jabuticaba peel for an extended period of time, the drying process is applied to remove water from the product and, consequently, reduce the risks of microbial growth and enzymatic reactions. The objectives of this study were to evaluate four drying models for spouted bed drying of jabuticaba peel using the following performance indicators: accuracy factor (Af), bias factor (Bf) and mean square error (RMSE), and analyze the impact of drying temperatures on the content of monomeric anthocyanins. The drying process was done in a pilot spouted bed dryer unit at temperatures: 50, 60 and 70°C for 2.5 h. The total monomeric anthocyanin content was determined using the pH differential method. It was observed that for the temperatures of 60°C and 70°C, the Two-term, and Page models, respectively, are appropriated to describe the drying kinetic of the jabuticaba peel in a spouted bed drying under the studied conditions. Moreover, for anthocyanins content, it was noted that there was a greater degradation at the highest temperature studied (70°C) as expected since anthocyanins are heat-sensitive substances.